Recently evolved combination of unique sulfatase and amidase genes enables bacterial degradation of the wastewater micropollutant acesulfame worldwide - Bonatelli, Maria L.; Rohwerder, Thore; Popp, Denny; Liu, Yu; Akay, Caglar; Schultz, Carolyn; Liao, Kuan-Po; Ding, Chang; Reemtsma, Thorsten; Adrian, Lorenz; Kleinsteuber, Sabine (Frontiers in Microbiology, 2023)
Xenobiotics often challenge the principle of microbial infallibility. One example is acesulfame introduced in the 1980s as zero-calorie sweetener, which was recalcitrant in wastewater treatment plants until the early 2010s. Then, efficient removal has been reported with increasing frequency. By studying acesulfame metabolism in alphaproteobacterial degraders of the genera Bosea and Chelatococcus, we experimentally confirmed the previously postulated route of two subsequent hydrolysis steps via acetoacetamide-N-sulfonate (ANSA) to acetoacetate and sulfamate. Genome comparison of wildtype Bosea sp. 100-5 and an acesulfame degradation-defective mutant revealed the involvement of two plasmid-borne gene clusters. The acesulfame-hydrolyzing sulfatase is strictly manganese-dependent and belongs to the metallo beta-lactamase family. In all degraders analyzed, it is encoded on a highly conserved gene cluster embedded in a composite transposon. The ANSA amidase, on the other hand, is an amidase signature domain enzyme encoded This is a provisional file, not the final typeset article in another gene cluster showing variable length among degrading strains. Transposition of the sulfatase gene cluster between chromosome and plasmid explains how the two catabolic gene clusters recently combined for the degradation of acesulfame. Searching available genomes and metagenomes for the two hydrolases and associated genes indicates that the acesulfame plasmid evolved and spread worldwide in short time. While the sulfatase is unprecedented and unique for acesulfame degraders, the amidase occurs in different genetic environments and likely evolved for the degradation of other substrates. Evolution of the acesulfame degradation pathway might have been supported by the presence of structurally related natural and anthropogenic compounds, such as aminoacyl sulfamate ribonucleotide or sulfonamide antibiotics.